KONSTRUKSI MAKNA KEPEMIMPINAN DIGITAL PADA ERA KECERDASAN BUATAN: KAJIAN FENOMENOLOGI TERHADAP PEMIMPIN PERUSAHAAN TEKNOLOGI DI INDONESIA - paeno paeno; Sutrisno Sutrisno; Hadi Winata (Jurnal Manajemen & Pendidikan [JUMANDIK], 2026)
The artificial intelligence era introduces profound transformations in organizational leadership practices, particularly within the technology sector operating at an unprecedented pace of disruption. This study aims to explore and understand the construction of digital leadership meanings from the subjective perspectives of technology company leaders in Indonesia who directly face challenges of AI integration in decision-making processes, team development, and organizational culture transformation. This research adopts a qualitative approach with Husserl's transcendental phenomenological design as its methodological foundation, enabling researchers to capture the essence of participants' lived experiences deeply and authentically. Data were collected through semi-structured in-depth interviews with twelve senior leaders of medium-to-large technology companies in Indonesia who have implemented AI solutions in their business operations for at least two years. Data analysis followed Moustakas's (1994) procedures encompassing epoche, phenomenological reduction, imaginative variation, and meaning synthesis. Findings reveal five essential meaning themes of digital leadership in the AI era: (1) leadership as navigation of algorithmic uncertainty; (2) data-based authority versus human intuition; (3) reconstruction of leader-subordinate relations in AI ecosystems; (4) leader identity at the crossroads of technology and humanism; and (5) leadership as a curator of AI ethical values. These findings enrich contemporary leadership theory by providing contextual indigenous perspectives on digital leadership dynamics in developing countries, while offering practical implications for AI-based leadership capacity development in Indonesia.